Prescription trend of antidiabetics among physicians and their selection according to lab investigations and physical parameters - Saba Rafique; Danish Shakoor; Ayesha Amjad; Syeda Zonish Ziadi; Ismat Younus; Maria Manan (AMMANIF, 2019)
While writing this article we observed 300 prescriptions of patients suffering from a number of different diabetic complications. Patients were from different family backgrounds but most of them belonged to Middle-class. We go through from the prescriptions and also analyzed them from their laboratory values and physical parameters. In the laboratory Investigations, we basically gave importance to Cholesterol level, ALT, Hba1c and creatinine levels .We asked from patients either they are taking their recommended medicines regularly ,we also asked them about the effect of medicines they observed . Most of the people were taking their medicines regularly but some were skipping their doses. After completing our survey we analyzed our data from different perspectives. We determined the generics mostly prescribed and then rank them according to their percentage of usage. After that we analyzed the change in trend of prescriptions due to disturbance in any of the above mentioned lab values. We also observed the changing trend of prescriptions according to their Body Mass Index(BMI) . In the end we gave it a conclusion that some of the classes of anti-diabetics are being prescribed in specific conditions and the rest of them are rarely used.